2019
DOI: 10.1111/vco.12457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multi‐agent chemotherapy protocol combining dexamethasone, melphalan, actinomycin D, and cytarabine for the treatment of resistant canine non‐Hodgkin high‐grade lymphomas: a single centre's experience

Abstract: The DMAC protocol (dexamethasone, melphalan, actinomycin‐D, cytarabine) has been evaluated in American studies for the treatment of relapsed canine lymphoma, comparing similarly to other rescue protocols. The aim of this study was to evaluate efficacy and toxicity of DMAC, in a larger UK cohort of resistant canine lymphomas. Medical records of dogs with resistant non‐Hodgkin high‐grade lymphomas that received DMAC as a rescue protocol were reviewed from 2007 to 2017. Response, time from initiation to discontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In domestic animals, the main uses are treatment of lymphoproliferative diseases and meningoencephalitis of unknown aetiology . Despite poor efficacy as a single agent in canine lymphoma, cytarabine may have a role to play in CNS (stage V) lymphoma, as it crosses the blood brain barrier .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In domestic animals, the main uses are treatment of lymphoproliferative diseases and meningoencephalitis of unknown aetiology . Despite poor efficacy as a single agent in canine lymphoma, cytarabine may have a role to play in CNS (stage V) lymphoma, as it crosses the blood brain barrier .…”
mentioning
confidence: 99%
“…15 In domestic animals, the main uses are treatment of lymphoproliferative diseases and meningoencephalitis of unknown aetiology. [17][18][19][20][21][22][23][24] Despite poor efficacy as a single agent in canine lymphoma, 23 cytarabine may have a role to play in CNS (stage V) lymphoma, as it crosses the blood brain barrier. 12,25,26 In addition, cytarabine intensification of induction protocols was associated with increased survival in a small number of patients with bone marrow (BM) infiltration.…”
mentioning
confidence: 99%
“…This route and dose was chosen because it is the predominant choice in previous multi-agent protocols involving cytarabine and is more practical in clinical practice. 13,21,26 Alvarez et al found no significant difference in response between subcutaneous or continuous rate infusion administration as part of the DMAC protocol in dogs (dexamethasone, melphalan, actinomycin D and cytosine arabinoside). 26 However, a pharmacokinetic study of cytarabine in healthy dogs showed that subcutaneous administration, compared with continuous IV administration, limits the ability to maintain steady-state concentrations and overall exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate and cytarabine have been used in multi-agent first-line and rescue protocols in both canine and feline lymphoma, are generally well tolerated and less myelosuppressive than lomustine. 3,13,[20][21][22] Based on these principles, the aim of this retrospective study was to assess the efficacy and tolerability of lomustine, methotrexate and cytarabine chemotherapy as rescue for feline lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…9,[16][17][18] Prednisone/prednisolone were prescribed at 1-2 mg/kg orally as indicated by the protocol. When CCNU was used as a rescue drug, previous chemotherapy consisted of either high-dose COP, 19 CHOP 20,21 or other rescue agents (e.g., anthracyclines, L-asparaginase, chlorambucil, vinca alkaloids, toceranib phosphate, DMAC protocol [22][23][24] ). Clinical data was collected for treatment of neutropenia/febrile neutropenia, including intravenous fluids, antibiotics, antipyretics and colony-stimulating factor (CSF) agents (e.g., filgrastim) as per the attending clinician's recommendation.…”
Section: Multidrug Chemotherapy Included Ccnu In Association Withmentioning
confidence: 99%